Iris Murdoch and the Immoralities of Adaptation. (23rd July 2022) - Wolfe, Graham
Abstract: Author of twenty-six novels between 1954 and 1995, Iris Murdoch ventured sporadically into theatre, completing two plays and adapting four of her novels. While she has been the subject of numerous articles and monographs, she has not received much critical attention for these theatrical efforts. Her adaptations, especially the two that she completed most independently— The Black Prince and The Sea, The Sea —are barely mentioned in critical accounts. Focusing on these two works, this article suggests not simply that a closer look reveals previously unperceived strengths and potentials; it argues that Murdoch's adaptations are provocative and worthy of further study precisely because they are so paradoxical, difficult to reconcile not only with her aesthetic concerns but with her philosophical and ethical positions. Put differently, while other novelists might write theatrical adaptations that are not very good, Murdoch's raise the question of whether adaptation may indeed be an immoral enterprise. Approaching The Black Prince and The Sea, The Sea from this angle will provoke a reconsideration of Murdoch's own critical writings on character and on the differing affordances of theatrical forms and novel forms, while also casting new light on the challenges of adapting first-person novels for the stage.